1983
DOI: 10.1111/j.1442-9993.1983.tb01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of damage by herbivorous insects on Eucalyptus trees

Abstract: High levels of insect damage on Eucalyptus have been noted but not quantified in previous literature. We present estimates of leaf damage for 44 Eucalyptus species from a variety-of habitats. Overall, an average of 15% of expanded leaf area was missing. While some species were generally lightly grazed, others, especially those in more mesic, higher altitude communities, usually sustained much heavier leaf damage. In the age and size classes, communities and years that we sampled, the overall levels of damage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
3

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 29 publications
1
55
3
Order By: Relevance
“…The amount of herbivory among species in communities has been estimated to commonly be about 10~, but is sometimes as high as 50 or 60~o of the leaf area removed (Reichle et al 1973;Fox & Morrow 1983). Thus, leaf-eating insects can have a significant, direct impact on plant carbon budgets because they consume photosynthetic tissue and consequently directly reduce carbon income.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of herbivory among species in communities has been estimated to commonly be about 10~, but is sometimes as high as 50 or 60~o of the leaf area removed (Reichle et al 1973;Fox & Morrow 1983). Thus, leaf-eating insects can have a significant, direct impact on plant carbon budgets because they consume photosynthetic tissue and consequently directly reduce carbon income.…”
Section: Introductionmentioning
confidence: 99%
“…Patterns consistent with the resource regulation hypothesis have also been found in eucalypts (Landsberg and Ohmart 1989) to which severe, repeated damage produces juvenile-form foliage that has higher levels of herbivory than adult foliage (Fox and Morrow 1983;Landsberg and Wylie 1983). Landsberg (1990) found that the younger foliage on eucalyptus trees suffering from the dieback syndrome was more nutritious and less well defended than that on unaffected trees.…”
Section: Introductionmentioning
confidence: 60%
“…However, I have been unable to find any reports of such attractants being more common in plants growing on infertile soils. In fact a recent general theory of plant-herbivore relationships suggests the reverse may be the case and that plants growing on infertile soils are especially well endowed with presumptive chemical defenses against herbivores (Janzen 1974;Feeny 1976;Rhoades & Cates 1976; but see Fox & Macauley 1977;Balick et al 1978;Morrow 1983).…”
Section: Accelerated Leaf Fallmentioning
confidence: 98%
“…A number of authors have argued that insect herbivory in Australian eucalypt forests is high in comparison with many overseas forest ecosystems; while rates between 10 and 70% have been measured in a number of eucalypt forests, rates of less than 10% seem more common in overseas plant communities (Morrow 1977;Springett l978;Journet 1981;Fox & Morrow 1983).…”
Section: Introductionmentioning
confidence: 98%